Integrasi Agama Dan Budaya Aceh Dalam Pembentukan Etos Kewirausahaan (Studi Kasus HIPMI dan KPMI Kota Langsa) - Sari, Nurhikmah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
This research aims to find out how the integration of religion and culture in the formation of entrepreneurial ethos entrepreneurs in langsa that joined in the organization. This research uses descriptive qualitative research methods. The results of this research is the ethos of entrepreneurs Aceh very creamy with the principle regiliusitas, the integration of religion in entrepreneurial ethos entrepreneurs langsa very visible where entrepreneurs predominantly langsa aceh believes that provision already God to manage, humans can only pray and will seek to pick up the biggest Obstacles entrepreneurs sustenance, langsa in implementing entrepreneurial ethos is to frequently affected by environmental guidelines that are considered too relaxed and underestimate the Affairs and consumer satisfaction.